2022
DOI: 10.3390/biomedicines10092245
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Selected Live Biotherapeutic Candidates to Inhibit the Interaction of an Adhesive-Invasive Escherichia coli Strain with Caco-2, HT29-MTX Cells and Their Co-Culture

Abstract: Adherent-invasive Escherichia coli (AIEC) has been implicated as a microbiological factor in the pathogenesis of inflammatory bowel disease (IBD). We evaluated the ability of six live biotherapeutic products (LBPs) to inhibit the interaction of an AIEC strain to three cell lines representing human gut epithelium. Co-inoculation of LBPs with AIEC showed a reduction in adhesion (up to 73%) and invasion of AIEC (up to 89%). Pre-inoculation of LBPs in HT-29-MTX and Caco-2 cells before challenging with AIEC further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…This strain has also been shown to be very effective in inhibiting adhesion of other enteric pathogens to cell lines representing the intestinal epithelium [ 53 ]. However, we have previously shown that there was no correlation between the F44A-1 AIEC adhesion and invasion of the co-culture cell model, and that this also did not correlate with the adhesion capabilities of live biotherapeutics products tested in that study [ 54 ]. For translocation assays we used E. coli strain HMLN-1, a highly efficient translocating strain as shown before [ 56 , 57 , 71 ], as a positive control.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…This strain has also been shown to be very effective in inhibiting adhesion of other enteric pathogens to cell lines representing the intestinal epithelium [ 53 ]. However, we have previously shown that there was no correlation between the F44A-1 AIEC adhesion and invasion of the co-culture cell model, and that this also did not correlate with the adhesion capabilities of live biotherapeutics products tested in that study [ 54 ]. For translocation assays we used E. coli strain HMLN-1, a highly efficient translocating strain as shown before [ 56 , 57 , 71 ], as a positive control.…”
Section: Discussionmentioning
confidence: 88%
“…It is generally accepted that probiotics are beneficial bacteria, competing with pathogens for binding sites and resources, essentially inhibiting them from colonising the gut epithelium [ 17 , 20 ]. Previous studies have shown probiotic strains as both a valuable prevention strategy and a therapeutic treatment option, reducing bacterial interaction with the gut epithelium [ 54 , 61 , 62 ]. Whilst many studies use a single cell line such as Caco-2 or HT-29 to assess the efficacy of probiotic strains in vitro, the lack of mucin production in these cell lines renders them suboptimal as a representation of the cell model of the GI tract when measuring bacterial colonisation [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be seen that Caco-2 and HT-29 cells with ratios of 1:0, 7:1, and 9:1 met the requirement of tissue integrity. Because of the benefits of the co-culture of Caco-2 and HT-29 cells, it provides the presence of both absorptive and goblet cells, both of which have different culture requirements for optimal growth and function to mimic intestine tissue in vivo [ 38 , 39 , 40 , 41 , 42 ]. Therefore, the ratio of 9:1 was selected based on the presence of both cell types and highest TEER value for subsequent uptake and transport studies.…”
Section: Resultsmentioning
confidence: 99%